Variasi Nilai Eksposi Aturan 15 Persen pada Radiografi Menggunakan Imaging Plate untuk Mendapatkan Kontras Tertinggi - Sartinah, Sartinah; Sumariyah, Sumariyah; Ketut Umiati, N. Ayu (BERKALA FISIKA, 2008)
The study about implementation of 15 % rule for getting the highest contrast of radiograph from Computed Radiography has been done.Computed Radiography that has been used in this research was Diagnost 65 Equipment with Step wedge as object, Imaging Plate as the storage system of digital data that will be treated to become image. Diagnost 65 Computed Radiography was operated with exposure factors such as;Â 50 kV/80 mAs, 60 kV/40mAs, 80 kV/10 mAs, 100 kV/2.5 mAs and 110 kV/1.25 mAs with plus and minus variation ofÂ 15 % voltage. Print out Radiograph by using Laser Printer was measured its densities by using densitometer. Value of densities and contras of exposure standard were compared with value of densities and contras of exposure with plus and minus variation of 15 % rule. By using contras obtained, the highest contrast was identified.The Results research show trend of densities value; its increase thick step wedge hence the density is smaller and increase thin step wedge hence the ever greater density. Highest radiograph contrast value got at various value exposure with voltage drop of tube 15% with twice of the current was multiplied the time. From this research yielded spread implementation of 15 % rule for computed radiography at various the exposure factors 60 kV-110kV. Keywords: 15%-rule, radiograph contrast